1990
DOI: 10.1680/geot.1990.40.1.45
|View full text |Cite
|
Sign up to set email alerts
|

Undrained stability of a trapdoor

Abstract: This paper examines the stability of a purely cohesive layer resting on a trapdoor. Although this problem has been studied for a number of years and is of considerable interest for analysing the stability of tunnels and mine workings, its exact collapse load is unknown. Rigorous bounds on the load needed to support the trapdoor against active failure are derived using two numerical techniques which employ finite elements in conjunction with the limit theorems of classical plasticity. Both of the methods assume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
5

Year Published

1996
1996
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(30 citation statements)
references
References 8 publications
2
23
0
5
Order By: Relevance
“…9(b) and straight line segments wereˆt through the data points. Both Pmin W Pi and Pult W Pi line segments showed a clear de‰ection point at about H W D=2, which corresponded well with analytical results by Davis (1968), Gunn (1980), and Sloan et al (1990). They concluded that when H W Dº2, the trapdoor is shallow, and when H W DÀ2, the trapdoor is deep.…”
Section: Ešect Of Overburden Heightssupporting
confidence: 86%
See 1 more Smart Citation
“…9(b) and straight line segments wereˆt through the data points. Both Pmin W Pi and Pult W Pi line segments showed a clear de‰ection point at about H W D=2, which corresponded well with analytical results by Davis (1968), Gunn (1980), and Sloan et al (1990). They concluded that when H W Dº2, the trapdoor is shallow, and when H W DÀ2, the trapdoor is deep.…”
Section: Ešect Of Overburden Heightssupporting
confidence: 86%
“…1g tests (Engesser, 1882;Terzaghi, 1936;McNulty, 1965;Ladanyi and Hoyaux, 1969;Evan, 1983;Tanaka and Sakai, 1993) and centrifuge tests under elevated acceleration levels (Stone and Wood, 1988;Craig, 1990;Iglesia, 1991;Abdulla and Goodings, 1994). Theoretical studies include solutions based on theory of elasticity (Finn, 1963;Chelapati, 1964), limit analysis (Davis, 1968;Gunn, 1980;Evan, 1983;Sloan et al, 1990; Singh and Basudhar, 1995; Smith, 1998), limit equilibrium (Engesser, 1882;Bierbaumer, 1913;Terzaghi, 1943;Krynine, 1945;Vardoulakis et al, 1981), andˆnite element analysis (Koutsabeloulis and Gri‹ths, 1989;Tanaka and Sakai, 1993;Nakai, et al, 1995). The focus of this paper is on physical model studies.…”
Section: Introductionmentioning
confidence: 99%
“…Installations are considered to correspond to deep burial conditions when the cover depth ratio H/D exceeds approximately 2.5 (Sloan et al 1990). The electromagnetic system holding the rigid trapdoor base in place was released during centrifuge testing.…”
Section: Centrifuge Testsmentioning
confidence: 99%
“…Vários pesquisadores têm estudado este fenômeno (NIELSON, 1967;GETZLER et al, 1968;BURGHIGNOLI, 1981;HANDY, 1985;SLOAN et al, 1990;OKO E YAMADA, 1993;MCKELVEY III, 1994;DANCYGIER E YANKELEVSKY, 1996;SANTICHAIANANT, 2002 (BULSON, 1985). Esta altura é definida com altura de igual recalque.…”
Section: Figura 25 -O Efeito Membranaunclassified
“…Entretanto, o entendimento global do fenômeno do efeito membrana é importante para deduzir e quantificar a sua influência no processo construtivo Geovala. Vários pesquisadores têm estudado este fenômeno (NIELSON, 1967;GETZLER et al, 1968;BURGHIGNOLI, 1981;HANDY, 1985;SLOAN et al, 1990; OKO E YAMADA, 1993;MCKELVEY III, 1994; DANCYGIER E YANKELEVSKY, 1996;SANTICHAIANANT, 2002 Em que: a = raio do duto; r = raio do arco formado na região de máxima tensão cisalhante.Conhecendo-se θ pode-se calcular o valor de dp. dp R sin dr r dr rsin…”
unclassified